Revealing the Inner World of Traumatized Children : an Attachment-Informed Model for Assessing Emotional Needs and Treatment. - Bradley, Christine (Jessica Kingsley Publishers, 2017)
This work provides an attachment-informed assessment and treatment model for understanding and responding to the emotional needs of traumatized children, based upon concepts deriving from the traditions of Winnicott and Bowlby and supported by current neuroscience and trauma research. Bringing together the latest research and theory about a child's inner world and the impact of the world around them, this is a guide to understanding and responding to the emotional needs of traumatised children. Founded on the principle that traumatised children do not have a secure sense of self and therefore cannot relate to the outside world without becoming overwhelmed, this book brings psychoanalytic and psychodynamic understandings of child psychology together with current neuroscience and trauma theory. At the heart of the book is an attachment-informed assessment model and guidance for treatment. Professionals working therapeutically with traumatised children, including therapists, psychologists, psychiatrists, mental health workers, social workers and residential care workers, will benefit from the wealth of knowledge and valuable practice guidance presented in this book.
Keywords: Abused children -- Rehabilitation.; Psychic trauma in children -- Treatment.; Child psychotherapy.; Community mental health services.; Children.; Neurodevelopmental Disorders -- therapy; Battered Child Syndrome -- psychology; Psychotherapy -- methods; Community Mental Health Services; Community Integration; Child; Adolescent; England; Traumatisme psychique chez l'enfant -- Traitement.; Enfants -- Psychothérapie.; Services communautaires de santé mentale.; Enfants.; children (people by age group); HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Community mental health services; Children; Psychic trauma in children -- Treatment; Abused children -- Rehabilitation; Child psychotherapy